2017
DOI: 10.1016/j.bjhh.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of Fanconi anemia patients after hematopoietic stem cell transplantation

Abstract: IntroductionFanconi anemia is a rare genetic disease linked to bone marrow failure; a possible treatment is hematopoietic stem cell transplantation. Changes in the nutritional status of Fanconi anemia patients are not very well known. This study aimed to characterize body composition of adult, children and adolescent patients with Fanconi anemia who were submitted to hematopoietic stem cell transplantation or not.MethodsThis cross-sectional study enrolled 63 patients (29 adults and 34 children and adolescents)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These alterations underscore the substantial physiological impact of HSCT on pediatric patients with β-TM. Studies have revealed that most children undergoing HSCT have normal BMI at admission, 36 however, decreases in BMI, and weight loss during the post-transplant weeks have been detected. 37 The American Society for Parenteral and Enteral Nutrition (A.S.P.E.N) and the European Society for Parenteral and Enteral Nutrition (E.S.P.E.N) have stated that children undergoing HSCT are at nutritional risk and that all children undergoing HSCT should be evaluated for nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations underscore the substantial physiological impact of HSCT on pediatric patients with β-TM. Studies have revealed that most children undergoing HSCT have normal BMI at admission, 36 however, decreases in BMI, and weight loss during the post-transplant weeks have been detected. 37 The American Society for Parenteral and Enteral Nutrition (A.S.P.E.N) and the European Society for Parenteral and Enteral Nutrition (E.S.P.E.N) have stated that children undergoing HSCT are at nutritional risk and that all children undergoing HSCT should be evaluated for nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that children with FA, especially males, can be naturally thin, although there is greater variability in weight than height (Figures 1 and 2). Low weight in individuals with FA may be due to nutritional deficits (Petryk et al, 2015), lower muscle mass (Silva et al, 2017), and lower bone mass (Giri et al, 2007); however, other studies have found normal bone mineral density (BMD) when…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that children with FA, especially males, can be naturally thin, although there is greater variability in weight than height (Figures 1 and 2). Low weight in individuals with FA may be due to nutritional deficits (Petryk et al, 2015), lower muscle mass (Silva et al, 2017), and lower bone mass (Giri et al, 2007); however, other studies have found normal bone mineral density (BMD) when adjusting for height age (Rose et al, 2012). Based upon the weight and BMI differences identified in our study and the increased risk of insulin resistance present in individuals with FA (Petryk et al, 2015), further studies characterizing lean and fat mass in FA are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Revista Brasileira de Hematologia e Hemoterapia , da Silva et al present data from a cross-sectional study evaluating a diverse set of body composition parameters in Fanconi Anemia patients aged 2–40 years, most of whom underwent HSCT. 9 The authors assessed BMI, referenced according to age in children and adolescents, and LBM of transplant recipients at various lengths of follow-up (0.5–27 years). They also analyzed a variety of complimentary assessment tools: triceps skin fold (TSF), arm circumference (AC), arm muscle area (AMA), and BIA with a standardized calculation for phase angle.…”
mentioning
confidence: 99%